2022
DOI: 10.3390/nu14173658
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Swallowing Disorders and Oral Malformations on Nutritional Status in Children with Cerebral Palsy

Abstract: Nutrition plays an important role both from a nutrition and a socio-psychological point of view; this part seems to be even more crucial in cerebral palsy where undernutrition is responsible for an increase in morbidity and mortality. The objective of this study was to evaluate the effects of swallowing disorders and oral malformations on the nutritional status of children with cerebral palsy. We evaluated 65 patients aged 2 to 17 years using a cross-sectional, descriptive and observational approach. All patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…It was found that swallowing disorders were found in 64.9% of children with CP. [ 31 ] Since numerous cancers are linked to dietary deficiencies, particularly vitamin deficiency,[ 1 ] infants with CP are likely more vulnerable to malignancy. A meta-analysis has revealed that the risk of liver cancer increases with vitamin D deficiency.…”
Section: Cerebral Palsy and Infant Growthmentioning
confidence: 99%
“…It was found that swallowing disorders were found in 64.9% of children with CP. [ 31 ] Since numerous cancers are linked to dietary deficiencies, particularly vitamin deficiency,[ 1 ] infants with CP are likely more vulnerable to malignancy. A meta-analysis has revealed that the risk of liver cancer increases with vitamin D deficiency.…”
Section: Cerebral Palsy and Infant Growthmentioning
confidence: 99%
“…Feeding problems that affect physical growth can be seen in children with CP due to reasons such as difficulty in sucking, chewing, and swallowing, loss of appetite, rejection of new foods, taking a long time to eat. If these feeding problems are not treated, they can cause growth and developmental retardation, which negatively affect morbidity and mortality [8,9].…”
Section: Introductionmentioning
confidence: 99%